2015
DOI: 10.1002/ejp.721
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the outcomes reported in multimodal pain therapy for chronic pain

Abstract: The current lack of standardization of outcome domains in MPT studies hinders to readily compare interventions from different trials and is a barrier towards evidence-based decision making. Based on these results, the development of a core outcome set of domains for MPT has been initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 82 publications
2
68
0
3
Order By: Relevance
“…For persistent low back pain, Kamper et al (2014) found MMR to be superior compared to other conservative treatments for pain and disability. Despite the fact that work is an important part of a person's social context, work-related aspects are seldom evaluated in interventions for persistent pain (Eccleston et al, 2014;Deckert et al, 2015;Heapy et al, 2015). Despite the fact that work is an important part of a person's social context, work-related aspects are seldom evaluated in interventions for persistent pain (Eccleston et al, 2014;Deckert et al, 2015;Heapy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For persistent low back pain, Kamper et al (2014) found MMR to be superior compared to other conservative treatments for pain and disability. Despite the fact that work is an important part of a person's social context, work-related aspects are seldom evaluated in interventions for persistent pain (Eccleston et al, 2014;Deckert et al, 2015;Heapy et al, 2015). Despite the fact that work is an important part of a person's social context, work-related aspects are seldom evaluated in interventions for persistent pain (Eccleston et al, 2014;Deckert et al, 2015;Heapy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At the time of the study, web-based interventions for pain management were rare, and no study involving web-based interventions added to MMR in clinical practice was published (MacEa et al, 2010;Rini et al, 2012;Eccleston et al, 2014). In addition, we chose to perform our study in primary healthcare, since most previous studies on this topic have evaluated MMR at specialized pain clinics (Kamper et al, 2014;Deckert et al, 2015). Considering this lack of information, we wanted to investigate the effects of a self-guided web-based intervention based on cognitive behavioural principles added to MMR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to thank Ruan et al (2016) for highlighting the increasingly important political issue related to the discussion on effectiveness and efficacy of multimodal pain therapy (MPT) on the basis of the systematic review on outcomes in MPT by Deckert et al (2016). We observe with concerns the current development of MPT programmes in the United States, as they were the cradle of this innovative therapeutic approach.…”
mentioning
confidence: 99%